A selfish glance of the novel Apolonio by Gustavo González Villanueva - Quesada Mora, Gabriel (2020)
The article consists of an analysis of the short novel Apolonio. Un politicodentro de la possible realidad de América Latina, written by the GuatemalanGustavo González Villanueva, according to the “lúdico-ambital” method,develop by the Spanish philosopher Alfonso López Quintás. We emphasizethe concepts of object/ambit and vertigo/ecstasy. Besides, we explore selfishthemes like reason, faith, and human relationships. This novel plays with anexistentialist dynamics regarding the characters thar vecome a philosophicalselfish density in a novelistic structure.